Energy‐efficient link resource allocation in the multibeam satellite downlink under QoS constraints. (6th January 2016) - Andreotti, Riccardo; Giannetti, Filippo; Luise, Marco
Summary: This work deals with the issue of boosting the capacity of digital subscriber line networks in the presence of geographical gaps. To this aim, an effective approach consists in exploiting the downlink of multibeam satellites for the delivering of packed‐based traffic, employing modulation and coding schemes denoted by very high spectral efficiency, such as in Digital Video Broadcasting‐Satellite, version 2 and eXtension standard, although time‐varying channel and interference may severely affect the quality of the communication. To cope with these issues, this paper proposes a novel link resource adaptation based on the following features. First, to efficiently manage packet‐based transmissions, an adaptive coding and modulation scheme is derived aimed at maximizing the 'goodput', that is, the offered layer‐3 data rate. Then, in order to mitigate the co‐channel interference arising from beams exploiting the same band, an adaptive power control is also proposed. The goal of the latter is to maximize the energy efficiency of the satellite downlink guaranteeing a given quality‐of‐service, that is, a minimum‐goodput, over each link. This problem is modeled as a non‐cooperative game, and the conditions of feasibility, existence, and uniqueness of the solution are analytically derived. Finally, simulation results are provided comparing the proposed strategy with the conventional rate satisfaction power control approach. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The paper proposes a novel adaptive coding and modulation scheme, based on DVB‐S2X standard, which ensure very high spectral efficiency, and an energy‐efficient power control (PC) algorithm to optimize the goodput over a multibeam satellite downlink. Results show performance improvement whenand compared withto conventional PC approaches based on rate satisfaction.